Ao Soberano Congresso: petições, requerimentos, representações e queixas à Câmara dos Deputados e ao Senado - os direitos do cidadão na formação do Estado Imperial brasileiro (1822 - 1831) - Pereira, Vantuil (2008)
In the present work intends to argue the insertion politics of the citizens in the Primeiro Reinado, beign satrted out to have had started a search for citizenship by means of to the presentation of petitions to the Senate and the House of representatives. A fight for the civil laws can be glimpsed, as well the construction of a certain perspective of citizenship. This work analyzes the fight politics of the period of 1822 the 1831, investigating the tensions that had involved the House, of representatives, The Imperial Senate and the proper Emperor, that debated the inherent attribuitions and limits to each one of the three to able constitutional. We also present an analysis of the petitions, having been possible to evidence the ambiguity and the Old Regimen and the quarrels on the constitutionalism, fruit of the revolutions initiated in the Europe in ends of century XVIII. We support that the presentation imperial parliament as atrategy of the petitioners face to the new occured institutional consolidation in the first years of the Independence of Brazil.